The Influence of Human Resource Empowerment and Competence on Employee Performance at the Office of Public Works and Spatial Planning of Sikka Regency - Maksimus Milianus Roly; Imanuel Wellem; Paulus Juru (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This research is grounded on the issue of employee performance seen from quality aspects of employees at the Public Works and Spatial Planning Office of Sikka Regency has not been maximized. This research aimed to: (1) determine the description of employee performance, human resource empowerment, and competence (2) analyze the influence of human resource empowerment and competency on employee performance either partially or simultaneously. The population in this research was 56 employees of the Public Works and Spatial Planning Office of Sikka Regency. Due to limited population, this research was conducted through census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing was done through the F-test and t-test. The results of descriptive statistical analysis showed that the response perception and employee performance variables, human resources empowerment, and competency were categorized as good. The results of the t-test showed that partially the human resource empowerment variable had a positive and significant influence on employee performance. The results of the F test showed that the variables of human resource empowerment and competency simultaneously significantly affected employee performance. The results of the determination analysis showed that the two independent variables in this research were able to explain the fluctuation of employee performance at the Public Works and Spatial Planning Office of Sikka Regency by 31.2% .